2007
DOI: 10.1111/j.1365-2613.2007.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia and reperfusion effects on skeletal muscle tissue: morphological and histochemical studies

Abstract: This was a study on the oxidative stress due to ischaemia (I) and reperfusion (R) in skeletal muscle tissue. Using a tourniquet, groups of rats were submitted to ischaemia for 4 h, followed by different reperfusion periods. The animals were divided in four groups: control; 4 h of ischaemia (IR); 4 h of ischaemia plus 1 h reperfusion (IR-1 h); 4 h of ischaemia plus 24 h reperfusion (IR-24 h); and 4 h of ischaemia plus 72 h reperfusion (IR-72 h). At the end of the procedures, samples of soleus muscle were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 40 publications
6
35
0
3
Order By: Relevance
“…In the present study, both the RH and LH showed significantly increased levels of carbonylated proteins at the 5th day, and decreased levels at the 10th day after tumour implantation. However, no significant differences were observed in the LH or RH when end products of lipid peroxidation were evaluated by TBARS [37]. To better evaluate membrane peroxidation and the significance of the change in membrane permeability in tumour-induced rats, the CL stimulated by tert-butyl hydroperoxide was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both the RH and LH showed significantly increased levels of carbonylated proteins at the 5th day, and decreased levels at the 10th day after tumour implantation. However, no significant differences were observed in the LH or RH when end products of lipid peroxidation were evaluated by TBARS [37]. To better evaluate membrane peroxidation and the significance of the change in membrane permeability in tumour-induced rats, the CL stimulated by tert-butyl hydroperoxide was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that ischemic morphological lesions are present minutes after reperfusion and increase progressively over time, due to an additional inflammatory response. In fact, cell death due to IRI is more evident after 4 hours of reperfusion, reaching the maximum peak at 24 hours 14,15 . In early reperfusion stages, most of the injury is associated with the acute release of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…These periods of reperfusion were selected based on previous studies focused on morphological and physiological recovery of the skeletal muscle tissue after ischemic injury [4,5,19,20]. The total sample size of 42 rats was determined based on 21 groups, significant level of 0.05 and confident level of 0.95.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In those cases, the muscles under the level of compression suffer the associated damage due to the ischemic condition followed by reperfusion injury [4,5]. The lesion patterns studied in myocytes after induced ischemia of two to four hours comprise edema, atrophy and changes in their surrounding connective tissue [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation